ITINERÁRIOS TERAPÊUTICOS EM CONSTRUÇÃO: Aids, Biomedicina e Religião - Pinho, Paula Andréa [UNIFESP] (2010)
The following text is an ethnography of the therapeutic itineraries of people with HIV/Aids. The goal is to make an approximation of the relationship between health/illness and religion, from the assessment of therapeutic constructed and experienced. The idea that guides the study is that, although biomedicine holds the legitimate monopoly of therapeutic solutions, it does not constitute a single reference for thinking about them. Therefore, assuming the existence of numerous therapies, the objective is to map the joints that are established between the biomedical and religious solutions in context of the epidemic. The ethnography at the Centro de Referência e Treinamento in STD/Aids in São Paulo – a center that serves HIV-infected patients – has shown complex itineraries in which the subjects use a range of therapies and blend biomedical treatments and religious therapies. The ethnographic enterprise tried to follow these paths and verify how these people represent, articulate and experience these therapies. For the patients from this study, the relationship announced between the categories of disease and treatment does not separate the religious and biomedical therapies: instead, it was observed a continuum between the two healing practices. And those who circulate among them by promoting the articulation of their symbols make them in their therapeutic itinerary always suitable for further transformation.